How can data from fitness trackers be obtained and analyzed with a forensic approach? - Hantke, Florian; Dewald, Andreas (Proceedings - 5th IEEE European Symposium on Security and Privacy Workshops, Euro S and PW 2020, 2020)
The use of Internet of Things devices is continuously increasing: People buy devices to make their lives more comfortable by using smart assistants or track sports activities and assess them. Moreover, these devices can sup-port digital investigators with valuable information when it is involved in a crime scene, since its data may provide information about the circumstances of the crime. One group of those devices are fitness trackers, which hold data such as walked steps. Accordingly, analysts can see activities, routines, and inconsistencies. We inspected three different common fitness trackers and developed a tool to analyze them in a standardized and forensically sound way. To collect data, we analyzed the Bluetooth communication, data on the phone, and internet communication. Our tool can analyze the different sources automatically and subsequently presents the results on a self-hosted web application. It is open-source and easily scalable so that developers can implement new extensions to support more than the three analyzed trackers.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Android; Bluetooth; Digital Forensics; Fitness Tracker; Internet of Things; Network